2003
DOI: 10.1046/j.1095-8649.2003.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated sperm morphology analysis in fishes: the effect of mercury on goldfish sperm

Abstract: This study is the first to examine the morphology of fish sperm using automated sperm morphology analysis (ASMA). The technique was applied to investigate the effect of an environmental pollutant, mercury, on the sperm morphology of goldfish Carassius auratus, and the effects on sperm morphology were compared with those on sperm motility. Goldfish sperm flagellar length was significantly shortened after instant exposure to 100 mg l−1 (368 µM) mercuric chloride, while curvilinear velocity (VCL) and the percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 39 publications
(49 reference statements)
0
58
1
4
Order By: Relevance
“…Van Look & Kime (2003) verificaram que a exposição dos espermatozoides de peixes em soluções crioprotetoras por 24 horas contendo crescentes níveis de cloreto de mercúrio causou injúrias nos espermatozoides e essas injúrias afetaram a motilidade dos espermatozoides, principalmente porque causaram diminuição do comprimento flagelar e aumento do tamanho da cabeça dos espermatozoides. Os autores atribuíram essas alterações ao fato de o mercúrio causar o rompimento dos microtubos que constituem os flagelos e da membrana plasmática que envolve a cabeça dos espermatozoides, promovendo assim um influxo de íons e soluções no interior da célula espermática.…”
Section: Resultsunclassified
“…Van Look & Kime (2003) verificaram que a exposição dos espermatozoides de peixes em soluções crioprotetoras por 24 horas contendo crescentes níveis de cloreto de mercúrio causou injúrias nos espermatozoides e essas injúrias afetaram a motilidade dos espermatozoides, principalmente porque causaram diminuição do comprimento flagelar e aumento do tamanho da cabeça dos espermatozoides. Os autores atribuíram essas alterações ao fato de o mercúrio causar o rompimento dos microtubos que constituem os flagelos e da membrana plasmática que envolve a cabeça dos espermatozoides, promovendo assim um influxo de íons e soluções no interior da célula espermática.…”
Section: Resultsunclassified
“…In similar work cad miu m (Cd) decreases the motility of carp spermatozoa in all tested concentrations, and that lethal effect was calculated 500 pp m by CASA Investigated the effects of Hg on sperms of goldfish (Carassius auratus) and discussed parameters of spermatozoa motility in terms of VCL value and spermatozoa morphology. According to the study, they found that concentrations of 1-10 mg/l mercury chloride (HgCl 2 ) significantly reduced VCL value of sperms and 100 mg/ l of HgCl 2 shortened the flagellu m length of spermatozoa (Van Look & Kime, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, automated sperm morphology analysis detected the altered morphologies of goldfish (Carassius auratus) sperm after cell exposure to mercuric chloride (Van Look and Kime, 2003). Likewise, the CASA results of cadmium-exposed spermatozoa of African catfish (Clarias gariepinus) showed that progressive motility was subsequently reduced (Kime, 1996).…”
Section: Sperm Quality Parametersmentioning
confidence: 99%